Oxidative Modification of Fibrinogen Affects Its Binding Activity to Glycoprotein (GP) IIb/IIIa - TETİK, ŞERMİN (SAGE PUBLICATIONS INC, 2010)
Aim: Proteins are sensitive biomarkers Of human diease condition associated with oxidative stress. Alteration of protein structures by oxidants may result ill partial or complete loss of protein functions. We have investigated the effect of structural modifications induced by metal ion catalyzed oxidation of Fibrinogen oil its binding capacity to glycoprotein IIb/IIIa (GpIIb/IIIa) and human platelets. Methods: We identified and quantified of binding capacity of native and oxidized fibrinogen to its receptor in vitro by flow cytometer. Dityrosine formation oil oxidized Fibrinogen were detected spectrophotometrically. Elevated degradation products Of fibrinogen after oxidation were revealed in the HPLC analysis. The native and oxidized fibrinogen were analyzed oil mass spectrum upon digestion with tyripsin. Results: Oxidatively modified fibrinogen showed less binding activity than native fibrinogen to GpIIb/IIIa coated micro beads and human platelets whereas slightly higher binding capaticity to ADP induced Stimulated platelets. Formation of dityrosines in the amino acid side chains of fibrinogen were observed Upon Oxidation. Decreased binding capacity of oxidized fibrinogen correlated with intensities of dityrosine formation. Oxidized fibrinogen had more ion-mass intensities at higher than native fibrinogen. Clinical implications: important point is decreased of binding capacity of the oxidized fibrinogen to own receptor. The decreased rate of binding, leading to effect in the diseases of clot formation May account for the association between oxidation of fibrinogen and the incidence of effect in human diseases.
Keywords: Oxidant stress; fibrinogen; GpIIb/IIIa; Flow Cytometry; HPLC- mass spectrum; PLATELET-AGGREGATION; PROTEINS